Ajustement structurel et effondrement des modèles idéologiques : Crise et renouveau de l'État africain - Souley, Abdoulaye (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1991)
The crisis of the State preceded structural adjustment, the latter only exposing a pre-existing economic and financial crisis. As a result of this financial crisis, the State’s ambitions have fallen into discredit. Its leaders are less able to redistribute wealth and, as one problem leads to another, their political survival is threatened. The « revolt of the belly » has been carried over to the political playing-field thanks to favourable international circumstances which have forced states to accept multipartygovernment. From this viewpoint, the collapse of ideological models and the structural policies of adjustment are as much factors in the crisis of the African State as they are in its renewal.